Impaired astrocytic synaptic function by peripheral cholesterol metabolite 27-hydroxycholesterol - Spanos, Fokion; Gerenu, Gorka; Goikolea, Julen; Latorre-Leal, María; Balleza-Tapia, Hugo; Gomez, Karen; Álvarez-Jiménez, Laura; Piras, Antonio; Gómez-Galán, Marta; Fisahn, André; Cedazo-Minguez, Angel; Maioli, Silvia; et al. (Frontiers in Cellular Neuroscience, 2024)
Astrocytes represent the most abundant cell type in the brain, where they play critical roles in synaptic transmission, cognition, and behavior. Recent discoveries show astrocytes are involved in synaptic dysfunction during Alzheimer´s disease (AD). AD patients have imbalanced cholesterol metabolism shown by high levels of side-chain oxidized cholesterol known as 27hydroxycholesterol (27-OH). Evidence from our laboratory has shown that elevated 27-OH can abolish synaptic connectivity during neuromaturation, but its effect on astrocyte function is currently unclear. Our results suggest that elevated 27-OH decreases the astrocyte function in vivo in Cyp27Tg, a mouse model of brain oxysterol imbalance. To study the relationship between astrocytes and neurons we have developed a 3D co-culture system that allows all the cell types from mice embryos to differentiate together in vitro. Here, we report a downregulation of glutamate transporters in the hippocampus of CYP27Tg mice together with increased GFAP. GLT-1 downregulation is also observed when WT mice were fed with high-cholesterol diets. We also report that our 3D co-cultures reproduce the effects of 27-OH observed in 2D neurons and in vivo.Moreover, we found novel degenerative effects in astrocytes that do not appear in 2D cultures together with the downregulation of glutamate transporters GLT-1 and GLAST. We propose this transporter dysregulation leads to neuronal hyperexcitability and synaptic dysfunction based on the effects of 27-OH on astrocytes. Taken together, these results report a new mechanism linking oxysterol imbalance in the brain and synaptic dysfunction through effects on astrocyte function.